2004
DOI: 10.1073/pnas.0307271101
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium-catalyzed asymmetric ring opening reactions of oxabicyclic alkenes: Catalyst and substrate studies leading to a mechanistic working model

Abstract: Catalyst and substrate studies have been performed on the rhodium-catalyzed asymmetric ring opening reaction. A working model is advanced that involves oxidative insertion with retention to form an organorhodium intermediate that then undergoes nucleophilic attack with inversion. Kinetic and competition experiments have uncovered evidence for a proton transfer step in the catalytic cycle that may activate both the allylrhodium intermediate and the nucleophile. We have also conducted experiments designed to und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
44
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(49 citation statements)
references
References 78 publications
3
44
1
1
Order By: Relevance
“…The successful application of aprotic silyl ketene acetals and enol ethers, acting as the nucleophiles, also supported such a process16. Though it was found that the reaction of an alkoxide or phenoxide does not give ring-opened products18, our calculations showed that the alkoxide can poison the catalyst by coordinating to the central Rh metal (Figure S9). As expected, the forming rhodium alkoxide complexes are quite stable thermodynamically, thus the substrates are inhibited from coordinating to the rhodium.…”
Section: Resultsmentioning
confidence: 54%
See 2 more Smart Citations
“…The successful application of aprotic silyl ketene acetals and enol ethers, acting as the nucleophiles, also supported such a process16. Though it was found that the reaction of an alkoxide or phenoxide does not give ring-opened products18, our calculations showed that the alkoxide can poison the catalyst by coordinating to the central Rh metal (Figure S9). As expected, the forming rhodium alkoxide complexes are quite stable thermodynamically, thus the substrates are inhibited from coordinating to the rhodium.…”
Section: Resultsmentioning
confidence: 54%
“…Once M3 has been formed, the rhodium alkoxide complex could be protonated by the alcohol prenucleophile to generate cationic rhodium complex and an alkoxide or phenoxide as proposed by Lautens et al . It was thought that the proton transfer has two effects: (i) the organorhodium species is made more electrophilic as a result of the obtained positive charge, and (ii) the nucleophile is rendered to be more nucleophilic by deprotonation18. Unfortunately, all of our efforts on locating such a transition state or intermediate concerning with proton transfer were failed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the previously established mechanistic model [23,77], we propose the following pathway for the formation of acrylate derivatives 3a and 3i (Scheme 4). In the presence of cationic phosphinogold(I) complex, a cationic intermediate A is formed by a regioselective opening of the oxygen bridge in substrate 1a .…”
Section: Resultsmentioning
confidence: 99%
“…1). Josiphos ligands provide chiral catalysts that display two types of chirality, planar and central [5,6]. The two types of chirality have been found to be advantageous in a number of catalytic applications such as asymmetric allylic aminations and the asymmetric reduction of b-bdisubstituted enoates [5].…”
Section: Introductionmentioning
confidence: 99%